The Enduring Popularity of Legacy Journalism: An Analysis of Online Audience Data - Nelson, Jacob L. (2020)
As news publishers continue to lose subscribers and advertising revenue, journalism practitioners and researchers have looked to newcomers to the field for ideas of how to adapt and succeed in a much more saturated and unstable media environment. Many have specifically looked to digital native news organizations to understand the ways that journalism is attempting to reinvent itself for a media landscape that is very different from the previous one. Yet what often gets lost in this focus on the newest news organizations is the resilience of many of journalism’s older ones. In this study, I analyze a year’s worth of U.S.-based online news consumption data to show that, even in a media environment increasingly saturated with digital native news outlets, legacy news brands continue to comprise a majority of the most popular news sites. Drawing on audience studies literature, I argue that these findings likely reflect audience preferences for familiar, established brands, as well as structural advantages these brands maintain due to their size and capital. I conclude that the fate of digital news organizations is not just a question of their innovativeness or nimbleness. It is also a question of their ability to combat a combination of powerful, stubborn forces: the habits of the people they hope to reach, and the deep pockets of their competitors.